THE RULE OF LAW AND ECONOMIC STABILITY AMID GLOBAL THREATS TO NATIONAL SECURITY - Dhara Syera Fatria; Parluhutan Sagala; Pujo Widodo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
National economic stability constitutes a fundamental pillar of national development and security. Global challenges, including trade wars, financial crises, and pandemics, have amplified the vulnerability of national economies. As a state governed by law, Indonesia bears a constitutional obligation to safeguard public welfare pursuant to the 1945 Constitution. This article analyzes the function of the rule of law in preserving economic stability as an integral component of national security strategy. The study employs a normative juridical method, examining constitutional mandates and regulations related to emergencies and economic regulation, namely the 1945 Constitution, Law No. 23/1959 on State of Emergency, Law No. 9/2016 on Prevention and Handling of Financial System Crises as updated by Law No. 4/2023 on Financial Sector Development and Strengthening (P2SK Law), and Law No. 3/2002 on National Defense. The findings reveal that Indonesia lacks an explicit legal recognition of economic emergencies as a distinct category. Consequently, legal reform is deemed necessary to ensure legitimacy, institutional clarity, and regulatory certainty in managing financial crises within the framework of national security.